Digitized Speech Characteristics in Patients with Maxillectomy Defects. Issue 6 (6th December 2017) - Elbashti, Mahmoud E.; Sumita, Yuka I.; Hattori, Mariko; Aswehlee, Amel M.; Taniguchi, Hisashi
Abstract: Purpose: Accurate evaluation of speech characteristics through formant frequency measurement is important for proper speech rehabilitation in patients after maxillectomy. This study aimed to evaluate the utility of digital acoustic analysis and vowel pentagon space for the prediction of speech ability after maxillectomy, by comparing the acoustic characteristics of vowel articulation in three classes of maxillectomy defects. Materials and Methods: Aramany's classifications I, II, and IV were used to group 27 male patients after maxillectomy. Digital acoustic analysis of five Japanese vowels—/a/, /e/, /i/, /o/, and /u/—was performed using a speech analysis system. First formant (F1) and second formant (F2) frequencies were calculated using an autocorrelation method. Data were plotted on an F1‐F2 plane for each patient, and the F1 and F2 ranges were calculated. The vowel pentagon spaces were also determined. One‐way ANOVA was applied to compare all results between the three groups. Results: Class II maxillectomy patients had a significantly higher F2 range than did Class I and Class IV patients ( p = 0.002). In contrast, there was no significant difference in the F1 range between the three classes. The vowel pentagon spaces were significantly larger in class II maxillectomy patients than in Class I and Class IV patients ( p = 0.014). Conclusion: The results of this study indicate that the acoustic characteristics of maxillectomy patients are affected by the defect area. This finding may provide information for obturator design based on vowel articulation and defect class.